A Review of Lumbar and External Ventricular Drainage in the Management of Meningitis. (16th November 2020) - Kilgore, Mitch; Carr, Christopher; Mathkour, Mansour H; Daban, Roxanne; Patel, Anand; Dumont, Aaron S
Abstract: INTRODUCTION: Meningitis is a neurological condition characterized by meningeal inflammation from various etiologies. The high mortality and morbidity seen in meningitis are predominantly due to brainstem compression and brain herniation secondary to associated intracranial pressure (ICP) elevation and communicating hydrocephalus. Neurosurgical interventions including lumbar and external ventricular drainage (LD/EVD) for cerebrospinal fluid (CSF) diversion have been used in treating meningitis. Nevertheless, no consensus has been made as to how these interventions should be routinely employed. METHODS: A review of PubMed was conducted to examine mechanisms, outcomes, and risks associated with LD/EVD in the setting of meningitis, with particular emphasis on indications and the advantages and disadvantages of each modality. RESULTS: Studies of mechanical CSF sterilization in bacterial meningitis demonstrated reduced CSF bacteria, leukocyte, and cytokine concentrations, as well as reductions in mortality and morbidity. LD and EVD were each noted to carry unique periprocedural risks. LD/EVD in the context of elevated ICP unrelated to meningitis were associated with secondary nosocomial infection, though this risk was three-fold higher for LD. Adjuvant LD/EVD in meningitis were associated with significantly reduced mortality and morbidity compared to conventional medical management. CONCLUSION: Adjuvant LD/EVD in meningitis is associated with reduced morbidity and mortality. This may be due to sustained reductions in ICP and/or elimination of pathogenic material. A threefold higher risk of secondary nosocomial infection burdens LD compared to EVD, although EVD carries greater periprocedural risk. Future investigations are needed to better elucidate which procedure is preferable. Both or either modality may be suitable therapies in meningitis patients that do not respond to pharmaceutical management as well as for CSF diversion on a case-by-case basis.